Perbandingan Fonologi Pada Bahasa Indonesia Dan Bahasa Jepang - Asti Dwi Ananta; Dinda Febrian; Nazwa Nadzilah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Phonology is a branch of linguistics that studies the sound system of language and examines the rules that regulate the use of language sounds based on their characteristics, such as articulation, frequency, duration, and intensity. This research discusses